M sub-shell X-ray fluorescence cross-section measurements in high Z elements with X-ray tube photon source - Gupta, Sheenu; Kaur, Gurpreet; Bansal, Himani; Mittal, Vijay Kumar; Mittal, Raj (European Journal of Chemistry, 2014)
X-ray tube has been used for selective M sub-shell excitations in a single reflection set-up for Pt, Au, Pb, Th and U required for M sub-shell fluorescence cross-sections measurements. Weighted photon energy and total intensity of the incident flux between EM5 edge and tube anode voltage were evaluated following a specific procedure. Comparison of measured cross-sections with the calculated ones from existing DHS/DF model based theoretical data on atomic parameters lend support to the present findings.